The Effect of Photobiomodulation Therapy in Different Doses on Bone Repair of Critical Size Defects in Rats: A Histomorphometric Study: Different Doses of PBM on Bone Repair - De Marco, Andrea; Torquato, Letícia; Gonçalves, Paulo Roberto; Ribeiro, Tatiana Camacho; Nunes, Camilla Moretto; Bernardo, Daniela Viscensotto; Gomes, Mônica Fernandes; Neves Jardini, Maria Aparecida; Santamaria, Mauro Pedrine (Journal of Lasers in Medical Sciences, 2021)
Introduction: Photobiomodulation therapy (PBM) appears to induce osteogenesis and stimulate fracture repair. This paper aims to analyze the effects of the PBM at different doses on the repair of critical bone defects through histological and histomorphometric analyses. Methods: Sixty 90-day-old adult rats (Rattus norvegicus, Albinus, Wistar) weighing approximately 300 g were used. Critical bone defects of 5 mm in diameter were performed in their calvaria. The animals were randomly separated into 5 groups: C-Blood clot, L15-PBM 15J/cm2, L30-PBM 30 J/cm2, L45-PBM 45 J/cm2, L60-PBM 60 J/cm2. Each group was subdivided according to observation periods of 30 and 60 days with 6 rats in each subgroup. Low-level gallium aluminum arsenide (GaAlAs) lasers were used at a 660 nm wavelength, 30 mW, and 0.04 cm2 in area. The PBM was applied over 5 points; 4 points of application were distributed on the edges while one point of application was located in the center of the bone defect. PBM occurred right after the procedure. In 30 and 60 days, the animals were euthanized by anesthesia overdose and the analyses were performed. The data were analyzed statistically by the ANOVA, together with the Tukey test, whose significance level was 5%. Results: As regards the treatment factor, the highest percentage of bone neoformation was achieved by group L45-60. The group with the highest closure, despite not having a statistically significant difference with the other doses, was 45 J with only 0.49 mm between edges. Conclusion: Thus, the present study allowed concluding that the highest percentage of bone neoformation area was achieved at 45 J/cm2 in 60 days; that is, it was significantly effective in comparison with other doses. DOI: 10.34172/jlms.2021.53.